Discursos sobre a creche na revista Pais e Filhos: análise da ideologia - Nazareth, Leila (2011)
This thesis shares one of the general purposes of NEGRI Núcleo de Estudos de Gênero, Raça e Idade, of the Post-Graduated Studies Program in Social Psychology of the PontifíciaUniversidadeCatólica de São Paulo PUCSP (Pontificial Catholic University of São Paulo), that is, to contribute to the understanding of the social construction of the Brazilian childhood. Specifically, the object of the study were the discourses about the baby, its education and care, in particular, produced and published by the magazine Pais e Filhos (Parents and Children), with the analysis of 40 years of the publication. The theoretical field was constituted with the integrations of John B. Thompson s theory of ideology (1995) and the studies about the construction of social problems. The theories of gender and the social studies about childhood contributed to the construction of the object. The methodology for the analysis of the symbolic production of Pais e Filhos was the depth hermeneutics (John B. Thompson, 1995), associated to techniques of analysis of content (Bardin, 1988). The results point to a silence about the theme small child and public space, which can be interpreted as an operation strategy of the ideology, acting in the maintenance of age inequalities. Babies and small children are presented as fragile and unprotected and their invisibility in public space, central theme of this thesis, is very little debated. The discourse, structured in a seducing way, reproducing a conversation with a friend, was identified as one more operation strategy of the ideology in the operation mode dissimulation. Day care centers are presented as a viable alternative so women consider them as the best option. Even when the reports encourage the use of this option, the text presents fears associated to the baby s fragility and to the aptitude of the institution to shelter it. The discourses that were produced and published by Pais e Filhos can be interpreted as agents of the support of domination relations of gender and age, contributing little to the modification of a inequalities scenario in relation to women and small children